Factors explaining the gender disparity in lipid-lowering treatment goal attainment rate in Chinese patients with statin therapy - Zhang Rui; Zhao Liancheng; Liang Lirong; Xie Gaoqiang; Wu Yangfeng (Lipids in Health and Disease, 2012)
Abstract Background The lipid-lowering treatment goal attainment rate is lower for women than for men among Chinese patients, but the reasons for this disparity have not been fully explored yet. Objectives To elucidate the potential factors and the significance of their contributions towards the observed discrepancy in lipid-lowering treatment goal attainment rates between Chinese women and men. Methods We used data from 1808 patients from 21 tertiary and 6 secondary hospitals in China who received and maintained statin therapy treatment for at least 2 months. Lipid-lowering treatment goal attainment was defined as low-density lipoprotein cholesterol (LDL- C) reaching the treatment targets recommended by the Chinese Guidelines on Prevention and Control of Dyslipidemia in Adults. Logistic Regression was used to explore possible factors associated with gender disparity in goal attainment rates, and to what extent each factor contributes. Results A total of 674 women and 1134 men were enrolled in the study. Women had a significantly lower LDL-C goal attainment rate than that of men (46.0% vs 53.8%, P = 0.002), particularly in high and very high CVD risk groups. Among high and very high risk patients, approximately 35%, 7%, 5%, and 5% of gender disparity in LDL-C goal attainment rate was attributable to the gender difference in baseline LDL-C level, cardiovascular co-morbidities and associated risk factors, socioeconomic status, and the dosage of statin treatment, respectively. Approximately 50% of the gender disparity remained unexplained by these factors. Conclusions Although nearly half of the gender disparity in lipid-lowering treatment goal attainment rate can be explained by the gender differences in baseline lipid level, socioeconomic status, cardiovascular co-morbidities and associated risk factors, and the dosage of statin in high and very high CVD risk patients, the other half of the gender disparity remains unexplained and requires further study to fully understand what other factors are at play.